(untitled) (Research, Society and Development, 2022)
Ginkgo biloba extract (GBE) has antioxidant, anti-inflammatory, and neuroprotective actions, and has a relaxing effect on smooth muscle organs. The vas deferens (DD) conducts the spermatozoa during ejaculation by the contraction of its muscles, and changes in this contraction can lead to disorders such as premature ejaculation (PE). PE is ejaculation that always or almost always occurs before or about 1 minute after vaginal penetration. Thus, our aim was to study the effect of GBE under the contraction of the DD of mice. The effect of GBE, here called GB2, or quercetin, was tested against contraction with potassium chloride. The effect of these substances was tested in the presence of nifedipine. We demonstrate that GB2, quercetin and nifedipine are able to inhibit the phasic and tonic components of the contraction. The effect of GB2 on the tonic component was enhanced in the presence of quercetin. Comparing the tonic component between GB2, Nifedipine+GB2 and Quercetin+GB2 groups, we observed that in the presence of nifedipine or quercetin, the effect of GB2 was potentiated. In the comparison of the Quercetin and Nifedipine+Quercetin groups, nifedipine potentiated the effect of quercetin under both components. These results indicate that GB2 and quercetin are able to inhibit some mechanism involved with the generation of DD contraction, and that this effect is not solely dependent on voltage-dependent calcium channel inhibition. These findings point out that GBE and quercetin, may be pharmacological strategies for the treatment of PE.